Work conditions and health of locomotive engineers. II. Questionnaire study, mortality and disability. - Hannunkari, Iris; Järvinen, Erkki; Partanen, Timo (Scandinavian Journal of Work, Environment & Health, 1978)
A questionnaire study on work conditions, work organization, leisure time, social problems, and health was directed toward active and retired locomotive engineers.This article mainly presents responses of the active engineers. The active locomotive engineers quoted the irregular work hours as the worst occupational problem. They judged noise and vibration in the locomotive cabs as disturbing. The majority of the desired changes in the work and work conditions concerned work time. The most common complaints given on the questionnaire were back trouble, hypertension and dermatitis. Tiredness and exhaustion were the most prevalent neuropsychological symptoms. A retrospective follow-up survey on invalidity and mortality was made. Trainmen and railroad clerks were used as reference cohorts.The engineers had relatively high invalidity and mortality rates in comparison to the reference groups, especially with respect to cardiovascular diseases and malignant tumors. Higher rates for disease of the digestive system and hearing loss were also suggested by the results.
Keywords: disability; health; locomotive engineer; mortality; questionnaire study; work condition